2016
DOI: 10.1515/eng-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Joining three car body steel sheets by clinching method

Abstract: Abstract:The optimization of a car body in terms of cost can be achieved by using different materials in various positions of the car in order to utilize specific properties of each different material. Resistance spot welding is the most used method of joining in car body production, but it is not always easy or even possible to join some combination of materials by this method. Clinching is an alternative method to spot welding, as a combination of drawing and forming. The research is focused on the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…At the same time, to validate the results in relation to the size of elements, a mesh sensitivity study was carried out to avoid the mesh distortion during the clinching process [123]. Figure 11(b) shows different tools including rectangular and round, these tools are regarded as rigid body, while single sheet, double sheets and three sheets are deformable bodies [57,124]. In general, the mechanical properties of the deformable bodies need to be analyzed exclusively.…”
Section: Simulation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, to validate the results in relation to the size of elements, a mesh sensitivity study was carried out to avoid the mesh distortion during the clinching process [123]. Figure 11(b) shows different tools including rectangular and round, these tools are regarded as rigid body, while single sheet, double sheets and three sheets are deformable bodies [57,124]. In general, the mechanical properties of the deformable bodies need to be analyzed exclusively.…”
Section: Simulation Analysismentioning
confidence: 99%
“…Because high-strength sheets are connected by using clinching technology, the punch wear will greatly influence the quality of clinched joint, so the tool wear will be tested and analyzed to avoid crack [56]. It is worth mentioning that L. Kašcák et al have found a double lock structure with three high-strength steel sheets that has higher strength in spite of a smaller mechanical lock [57]. Although the three high-strength steel sheets were joined by clinching method successfully, the application of this combination needs to be further excavated.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom thickness (X ), exterior protrusion height (H ), neck thickness (t n ), and interlock value (t s ) are the main geometric parameters of the joints. 31,[34][35][36] The height of the exterior protrusion affects the application field and aesthetics of the clinched joint, while the interlock value (t s ) and the neck thickness (t n ) affect the failure mode and static strength of the clinched joint directly.…”
Section: Mechanism Of Mechanical Clinching With Extensible Diesmentioning
confidence: 99%
“…Not only two sheets, but also three sheets are joined by mechanical clinching. Kaðèák et al have joined the three steel sheets [ 43 ] and a sheet combination including the high strength steel and aluminium alloy sheets [ 44 ]. However, the three sheets including the ultra-high strength and aluminium alloy sheets are not tried.…”
Section: Introductionmentioning
confidence: 99%